2013
DOI: 10.1016/s2213-8587(13)70049-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor imaging for the localisation of insulinomas: a prospective multicentre imaging study

Abstract: Oncosuisse, the Swiss National Science Foundation, and UK Department of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
161
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(167 citation statements)
references
References 24 publications
2
161
1
3
Order By: Relevance
“…Several series have described imaging findings consistent with nesidioblastosis (Christ et al 2013, Figure 5 A 59-year-old woman with endogenous hyperinsulinaemic hypoglycaemia referred for 68 Ga-DOTA-exendin-4 PET/CT for insulinoma localisation. Axial PET images (A) demonstrate focal intense uptake extending from the anterior margin of the left kidney (yellow circles), corresponding to an exophytic density arising from the pancreatic tail on fused PET/CT (B) and low dose CT (C) images.…”
Section: :6mentioning
confidence: 99%
See 1 more Smart Citation
“…Several series have described imaging findings consistent with nesidioblastosis (Christ et al 2013, Figure 5 A 59-year-old woman with endogenous hyperinsulinaemic hypoglycaemia referred for 68 Ga-DOTA-exendin-4 PET/CT for insulinoma localisation. Axial PET images (A) demonstrate focal intense uptake extending from the anterior margin of the left kidney (yellow circles), corresponding to an exophytic density arising from the pancreatic tail on fused PET/CT (B) and low dose CT (C) images.…”
Section: :6mentioning
confidence: 99%
“…The median reduction in the blood glucose level was 1.3 mmol/L (range 0.8-2.1 mmol/L) with a nadir occurring approximately 40 min after injection in a large series of patients imaged for insulinoma localisation with 111 In-exendin-4 (Christ et al 2013). Twenty of 30 patients in this study required exogenous glucose infusion for hypoglycaemia, whereas more recent studies (Antwi et al 2015, Luo et al 2016 routinely co-administer glucose infusion in all patients to minimise the risk of hypoglycaemia.…”
Section: :6mentioning
confidence: 99%
“…Furthermore, in a prospective multicentric study conducted by Christ et al,using 111 In-diethylenetriaminepentaacetic acid-exendin-4 for single-photon-emission CT examination, a transient exacerbation of hypoglycemia was reported (20). A large, prospective cohort study by Luo et al, using 68 Galabeled exendin-4 derivative, also showed promising sensitivity for PET/CT when compared to other imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…GLP1 analogs have recently been shown to possess great sensitivity in the detection of insulinomas (20,21). Furthermore, in a prospective multicentric study conducted by Christ et al,using 111 In-diethylenetriaminepentaacetic acid-exendin-4 for single-photon-emission CT examination, a transient exacerbation of hypoglycemia was reported (20).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, malignant insulinomas often do express sst 2 , which can be targeted using SRS (24,60,61,62,63,64,65,66). In various studies, GLP1R scintigraphy using 111 In-DOTAexendin-4 successfully detected benign insulinomas (60,67,68,69,70). This radiopharmaceutical can also be successfully applied for the intraoperative localisation of these benign tumours (68).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%